PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA GURU DIMODERASI SUPERVISI KEPALA SEKOLAH DI SD SE KECAMATAN BATANG KABUPATEN BATANG - Sujiani, 12.5202.0117 (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to analyze the influence Influence of Work Motivation and Discipline Supervision on Teacher Performance Moderated Elementary Principal at one-District of Batang. In this study population of all primary school teachers in the District of Batang PNS, whereas the sample used was 126 persons as respondents to the census technique. With a respondent criteria PNS Elementary Teachers in the District Education Office Trunk Unit. Measurements using a Likert scale of 7 (seven) alternative answers. Test instruments used are validity and reliability. While the test model used is the coefficient of determination and F test (goodnes of Fit). Test this hypothesis using regression analysis. Based on the results of the study can be summarized as follows: (i) Motivation no impact on teacher performance, (ii) Work Discipline has no effect on teacher performance, (iii) (ii) Supervising Principal has no effect on teacher performance, (iv)Supervising Principal does not moderate the effect of motivation on teacher performance, and (v) Principal supervision Work Discipline does not moderate the influence of the Teacher Performance Keywords:Â  Work Motivation, Work Discipline, Supervising Principal, and Teacher Performance.